Fullerene composite material and preparation method thereof, perovskite solar cell and preparation method thereof, and electric device
Patent Information
- Application Number
- CN202380054279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-01
AI Technical Summary
The photoelectric conversion efficiency of the electron transport layer prepared from pure fullerene and its derivatives in existing perovskite solar cells is low and difficult to effectively improve.
A fullerene composite material is formed by embedding the doping material of the second fullerene and fullerene derivative into the crystal lattice of the first fullerene and fullerene derivative, and uniformly mixing it in the solvent using a heat treatment method To improve doping uniformity and prepare electron transport layers for perovskite solar cells.
It significantly improves the conductivity of fullerene composite materials and improves the photoelectric conversion efficiency of perovskite solar cells, and the appropriate proportion of doping materials can effectively avoid affecting the structure of the main material.
Smart Images

Figure CN119631604A_ABST
Abstract
Description
Fullerene composite material and preparation method thereof, perovskite solar cell and preparation method thereof, and electrical device Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a fullerene composite material and a preparation method thereof, a perovskite solar cell and a preparation method thereof, and an electrical device. Background Art
[0002] With the continuous development of solar cell research, perovskite solar cells have attracted widespread attention due to their high photoelectric conversion efficiency and relatively simple preparation process.
[0003] Fullerenes and their derivatives are commonly used electron acceptors in perovskite solar cells. However, as research on perovskite solar cells continues to deepen, the photoelectric conversion efficiency of cells prepared using pure fullerenes and their derivatives as the electron transport layer in perovskite solar cells remains low.
[0004] Summary of the Invention
[0005] According to various embodiments of the present application, the present application provides a fullerene composite material, including a host material and a dopant material, wherein the host material includes at least one of a first fullerene and a first fullerene derivative, and the dopant material is selected from at least one of a second fullerene and a second fullerene derivative, and the molecular structure of the dopant material has a partial structure embedded in the lattice of the first fullerene and / or the first fullerene derivative.
[0006] In the present application, by doping a host material comprising a first fullerene and / or a first fullerene derivative with at least one of a second fullerene and a second fullerene derivative, the conductivity of the fullerene composite material can be increased, thereby improving the photoelectric conversion efficiency of the perovskite solar cell.
[0007] In some embodiments, the mass percentage of the dopant material is 0.0001% to 1% based on the total mass of the first fullerene and / or the first fullerene derivative and the dopant material. If the mass percentage of the dopant material is too small, the doping effect is poor, while if the mass percentage of the dopant material is too large, it may have a significant impact on the intrinsic structure of the host material.
[0008] In some embodiments, the first fullerene comprises at least one of C50, C60, and C70, and the first fullerene derivative comprises at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM, and PC72BM. These fullerenes and fullerene derivatives are widely available and easy to obtain.
[0009] In some embodiments, the second fullerene comprises at least one of C50, C60, and C70, and the second fullerene derivative comprises at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM, and PC72BM. These fullerenes and fullerene derivatives are readily available from a wide variety of sources.
[0010] The present application also provides a method for preparing a fullerene composite material, comprising the following steps:
[0011] mixing the first raw material and the second raw material in a first solvent, and heat-treating the resulting mixed system;
[0012] The first raw material contains a first fullerene and / or a first fullerene derivative and / or a raw material for synthesizing the first fullerene derivative, and the second raw material contains at least one of a second fullerene and a second fullerene derivative used as a doping material.
[0013] In this preparation method, adding the doping material to the reaction system before heat treatment allows the doping material to be more evenly dispersed throughout the reaction system. In the resulting fullerene composite material, the doping material is more evenly doped into the first fullerene derivative, reducing the risk of doping material agglomeration and improving doping uniformity.
[0014] In some embodiments, the raw materials for synthesizing the first fullerene derivative include a third fullerene, methyl 5-phenyl-5-(p-toluenesulfonylhydrazide)pentanoate, and a base; mixing the first raw material and the second raw material in a solvent includes:
[0015] The methyl 5-phenyl-5-(p-toluenesulfonylhydrazide)valerate and the base are dispersed in a first sub-solvent, the second raw material and the third fullerene are dispersed in a second sub-solvent, and the two solution systems are mixed.
[0016] In some embodiments, the molar ratio of the third fullerene, the doping material, the 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and the base is 1:(10 -5 ~10 -2 ):(1~2):(1~10).
[0017] In some embodiments, the first sub-solvent comprises pyridine.
[0018] In some embodiments, the second sub-solvent includes at least one of toluene, xylene, chlorobenzene, and dichlorobenzene.
[0019] In some embodiments, the base includes at least one of sodium methoxide, cesium carbonate, sodium hydroxide, and potassium hydroxide.
[0020] In some embodiments, the first solvent includes at least one of toluene, xylene, chlorobenzene, and dichlorobenzene.
[0021] In some embodiments, the heat treatment temperature is 100°C to 300°C.
[0022] In some embodiments, the heat treatment time is 24 hours to 60 hours.
[0023] In some embodiments, the heat treatment comprises heating under reflux.
[0024] The present application also provides a perovskite solar cell, comprising a first electrode, a perovskite layer, an electron transport layer, and a second electrode stacked in sequence;
[0025] The electron transport layer includes the fullerene composite material, or
[0026] The electron transport layer comprises the fullerene composite material obtained by the preparation method.
[0027] In the above-mentioned perovskite solar cell, the electron transport layer includes a fullerene composite material, which can improve the performance of the perovskite solar cell.
[0028] In some embodiments, the thickness of the electron transport layer is 10 nm to 100 nm.
[0029] The present application also provides a method for preparing a perovskite solar cell, comprising the following steps:
[0030] forming a perovskite layer on the first electrode;
[0031] preparing an electron transport layer on the perovskite layer;
[0032] preparing a second electrode on the electron transport layer;
[0033] The electron transport layer includes a fullerene composite material, which includes a main material and a dopant material. The main material includes at least one of a first fullerene and a first fullerene derivative, and the dopant material is selected from at least one of a second fullerene and a second fullerene derivative. The molecular structure of the dopant material has a partial structure embedded in the crystal lattice of the first fullerene and / or the first fullerene derivative.
[0034] The present application also provides an electrical device comprising the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0036] FIG1 is a schematic structural diagram of an exemplary perovskite solar cell.
[0037] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered to limit the scope of the disclosed inventions, the presently described embodiments and / or examples, and any of the best modes currently understood for these inventions. DETAILED DESCRIPTION
[0038] The following describes the perovskite solar cell, its preparation method, and its power-consuming device in further detail with reference to specific examples. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to facilitate a more thorough and comprehensive understanding of the present disclosure.
[0039] The details of one or more embodiments of the present application are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0041] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0043] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0045] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0046] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0047] If not otherwise specified, in this application, the term "room temperature" generally refers to 4°C to 30°C, preferably 25±5°C.
[0048] The present application provides a fullerene composite material, comprising a host material and a dopant material, wherein the host material comprises at least one of a first fullerene and a first fullerene derivative, and the dopant material is selected from at least one of a second fullerene and a second fullerene derivative, wherein a molecular structure of the dopant material is partially embedded in the lattice of the first fullerene and / or the first fullerene derivative.
[0049] In the fullerene composite material of the present application, a host material including a first fullerene and / or a first fullerene derivative is doped with at least one of a second fullerene and a second fullerene derivative. In the composite material, a portion of the molecular structure of the doping material is embedded in the crystal lattice of the first fullerene and / or the first fullerene derivative, thereby increasing the conductivity of the fullerene composite material and improving the photoelectric conversion efficiency of the perovskite solar cell.
[0050] In fullerene derivatives, the presence of side chains can increase the distance between molecules, making carrier extraction difficult and hindering the improvement of the fullerene derivative's conductivity. The molecular structure of the doping material, partially embedded within the lattice of the first fullerene and / or the first fullerene derivative, can reduce the distance between molecules, enhance electron transport, and improve the conductivity of the fullerene composite material.
[0051] It is understood that the first fullerene and the second fullerene may be the same or different, and the first fullerene derivative and the second fullerene derivative may be the same or different.
[0052] In some embodiments, the first fullerene comprises at least one of C50, C60, and C70. The first fullerene derivative comprises at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM, and PC72BM. The second fullerene comprises at least one of C50, C60, and C70. The second fullerene derivative comprises at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM, and PC72BM. These fullerenes and fullerene derivatives are readily available from a wide variety of sources.
[0053] It is also understood that fullerene derivatives are typically obtained by modifying fullerenes, wherein the fullerene lattice is typically spherical, so that the fullerene derivative's lattice also primarily exhibits a spherical shape. When the molecular structure of the dopant material is partially embedded in the lattice of the first fullerene and / or the first fullerene derivative, it can be manifested as the molecular structure of the dopant material being partially embedded in the spherical lattice of the first fullerene and / or the first fullerene derivative. Alternatively, when the dopant material has side chains, the side chains of the dopant material are embedded in the lattice of the first fullerene and / or the first fullerene derivative. It is understood that fullerene derivatives are typically obtained by modifying fullerenes such as C50, C60, and C70.
[0054] It can also be understood that when a portion of the molecular structure of the doping material is embedded in the crystal lattice of the first fullerene and / or the first fullerene derivative, the remaining structure of the molecular structure of the doping material may extend from the crystal lattice of the first fullerene and / or the first fullerene derivative, or may be attached to the outer surface of the crystal lattice of the first fullerene and / or the first fullerene derivative.
[0055] In some embodiments, the mass percentage of the dopant material, calculated as a percentage of the total mass of the first fullerene and / or the first fullerene derivative, and the dopant material, is 0.0001% to 1%. Alternatively, the mass percentage of the dopant material, calculated as a percentage of the total mass of the first fullerene and / or the first fullerene derivative, and the dopant material, is 0.0001%, 0.001%, 0.01%, 0.02%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. If the mass percentage of the dopant material is too small, the doping effect is poor, while if the mass percentage of the dopant material is too large, it may have a significant impact on the intrinsic structure of the host material.
[0056] Optionally, the type and content of the doping material can be measured by liquid chromatography. Optionally, the liquid chromatography conditions are: a 15 cm long C18 directional column, a mobile phase of toluene:methanol = 1:2, and a DAD detector.
[0057] In the present application, the mass percentage of the doping material based on the total mass of the first fullerene and / or the first fullerene derivative and the doping material may be recorded as the doping amount of the doping material.
[0058] In some embodiments, the fullerene composite material comprises a host material and a dopant material, wherein the host material is selected from at least one of a first fullerene and a first fullerene derivative, and the dopant material is selected from at least one of a fullerene and a second fullerene derivative. The molecular structure of the dopant material is partially embedded within the crystal lattice of the first fullerene and / or the first fullerene derivative. Optionally, the mass percentage of the dopant material, calculated as a percentage of the total mass of the first fullerene and / or the first fullerene derivative and the dopant material, is 0.0001% to 1%. Optionally, the mass percentage of the doping material, measured as a percentage of the total mass of the first fullerene and / or the first fullerene derivative, and the doping material, is 0.0001%, 0.001%, 0.01%, 0.02%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0059] This application also provides a method for preparing a fullerene composite material. The method comprises the following steps: mixing a first raw material and a second raw material in a first solvent, and heat-treating the resulting mixture; wherein the first raw material comprises a first fullerene and / or a first fullerene derivative and / or a raw material for synthesizing the first fullerene derivative, and the second raw material comprises at least one of a fullerene used as a doping material and a second fullerene derivative.
[0060] When preparing fullerene composite materials, agglomeration of the doping material is a significant factor affecting the composite's performance. In this preparation method, adding the doping material to the reaction system before heat treatment allows for a more uniform dispersion of the doping material within the reaction system. In the resulting fullerene composite material, the doping material is more evenly incorporated into the first fullerene derivative, reducing the risk of agglomeration and improving doping uniformity.
[0061] In some embodiments, the first raw material contains a raw material for synthesizing a first fullerene derivative, and the raw material for synthesizing the first fullerene derivative includes a third fullerene, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate, and a base; mixing the first raw material with the second raw material in a solvent includes: dispersing 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and the base in a first sub-solvent, dispersing the second raw material and the third fullerene in a second sub-solvent, and mixing the two solution systems.
[0062] Optionally, the third fullerene includes at least one of C50, C60 and C70. Optionally, the first fullerene, the second fullerene and the third fullerene may be different from each other or may be completely the same.
[0063] In some embodiments, the molar ratio of the third fullerene, the doping material, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and the base is 1:(10 -5 ~10 -2 ): (1-2): (1-10). Optionally, the molar ratio of the third fullerene, the doping material, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and the base is 1:10. -5 : 1:1, 1:10 -5 : 1:5, 1:10 -5 : 1:8, 1:10 -4 : 1:1, 1:10 -4 : 1:5, 1:10 -4 : 1:8, 1:10 -3 : 1:1, 1:10 -3 : 1:5, 1:10 - 3 : 1:8, 1:10 -2 : 1:1, 1:10 -2 : 1:5, 1:10 -2 :1:8, etc.
[0064] In some embodiments, the first sub-solvent comprises pyridine.
[0065] Optionally, the second sub-solvent includes at least one of toluene, xylene, chlorobenzene, and dichlorobenzene. The xylene includes at least one of o-xylene, m-xylene, and p-xylene. The dichlorobenzene includes at least one of o-dichlorobenzene, m-dichlorobenzene, and p-dichlorobenzene.
[0066] Optionally, the base includes at least one of sodium methoxide, cesium carbonate, sodium hydroxide and potassium hydroxide.
[0067] Optionally, the raw materials for synthesizing the first fullerene derivative include the third fullerene, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and a base; mixing the first raw material and the second raw material in a solvent includes: adding 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate to a first sub-solvent, then adding a base, stirring, and evacuating the gas to place the solution system under an argon atmosphere; adding the second raw material and the third fullerene to the second sub-solvent, and then adding the resulting solution to a solution system containing the first sub-solvent.
[0068] Alternatively, the raw materials used to synthesize the first fullerene derivative include a third fullerene, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate, and a base. The first raw material and the second raw material are mixed in a first solvent, and the resulting mixed system is heat-treated, further comprising: removing the solvent from the product obtained after the heat treatment, and then separating the product. Alternatively, the solvent can be removed by rotary evaporation. Alternatively, the product can be separated by column chromatography.
[0069] In some embodiments, the first raw material is a first fullerene derivative. The mass percentage of the dopant material, calculated as a percentage of the total mass of the first fullerene derivative and the dopant material, is 0.0001% to 1%. Alternatively, the mass percentage of the dopant material, calculated as a percentage of the total mass of the first fullerene derivative and the dopant material, is 0.0001%, 0.001%, 0.01%, 0.02%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or the like.
[0070] Optionally, the first raw material is a first fullerene derivative. The first raw material and the second raw material are mixed in a first solvent, and the resulting mixed system is heat-treated, further comprising: concentrating the product obtained after the heat treatment, and then adding methanol to precipitate the product. The precipitation yields a fullerene composite material.
[0071] In some embodiments, the first solvent includes at least one of toluene, xylene, chlorobenzene, and dichlorobenzene. The xylene includes at least one of o-xylene, m-xylene, and p-xylene. The dichlorobenzene includes at least one of o-dichlorobenzene, m-dichlorobenzene, and p-dichlorobenzene.
[0072] In some embodiments, the heat treatment temperature is 100° C. to 300° C. The heat treatment time is 24 hours to 60 hours. The heat treatment includes heating under reflux. Alternatively, the heat treatment temperature is 100° C., 120° C., 150° C., 180° C., 200° C., 220° C., 250° C., 280° C., 300° C., etc. The heat treatment time is 24 hours, 30 hours, 36 hours, 48 hours, 60 hours, etc.
[0073] In some embodiments, the preparation method of 5-phenyl-5-(toluenesulfonylhydrazide) methyl pentanoate comprises: mixing methyl 4-benzoylbutyrate, toluenesulfonylhydrazide, and methanol, heating under reflux for reaction, cooling to room temperature, shielding from light, then transferring to -15°C and shielding from light overnight, filtering, and recrystallizing the product from methanol. The product is vacuum-treated at 40°C overnight to obtain 5-phenyl-5-(toluenesulfonylhydrazide) methyl pentanoate as a white solid. Optionally, the heating under reflux reaction time is 12 hours, and after cooling to room temperature, shielding from light and storing for 24 hours.
[0074] In some embodiments, the preparation method of methyl 4-benzoylbutyrate includes: dissolving benzoylbutyric acid in chlorobenzene, adding methanol, stirring until completely dissolved, adding hydrochloric acid dropwise, continuing stirring, heating under reflux to react overnight, stopping stirring, neutralizing with saturated sodium carbonate until there are no bubbles, separating the oil and water, and then extracting the aqueous phase with ethyl acetate, combining the organic phases, removing water with anhydrous calcium chloride, distilling off the solvent under reduced pressure, eluting and separating the product on a silica gel column, the eluent is ethyl acetate and n-hexane, wherein the volume ratio of ethyl acetate to n-hexane is 3:1, to obtain a light yellow oily liquid methyl 4-benzoylbutyrate.
[0075] The present application also provides an electron transport film. The electron transport film comprises the above-described fullerene composite material or the fullerene composite material obtained by the above-described method for preparing the fullerene composite material. Optionally, the electron transport film has a thickness of 10 nm to 100 nm. Further optionally, the electron transport film has a thickness of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0076] The present application also provides an electron transport slurry. The electron transport slurry includes a second solvent and the fullerene composite material described above or a fullerene composite material obtained by the method for preparing the fullerene composite material described above. Optionally, the second solvent in the electron transport slurry includes at least one of toluene, xylene, chlorobenzene, and dichlorobenzene. The xylene includes at least one of o-xylene, m-xylene, and p-xylene. The dichlorobenzene includes at least one of o-dichlorobenzene, m-dichlorobenzene, and p-dichlorobenzene.
[0077] The present application also provides a perovskite solar cell. The perovskite solar cell comprises a first electrode layer, a perovskite layer, an electron transport layer, and a second electrode layer stacked in sequence. The electron transport layer comprises the above-mentioned fullerene composite material, or the electron transport layer comprises the fullerene composite material obtained by the above-mentioned preparation method, or the electron transport layer comprises the above-mentioned electron transport film, or the electron transport layer is prepared from a material including the above-mentioned electron transport slurry. In a perovskite solar cell, the electron transport layer comprises the fullerene composite material, which can improve the performance of the perovskite solar cell.
[0078] Optionally, the electron transport layer is prepared by spin coating and annealing a material including the electron transport paste. Further, the electron transport layer is prepared by spin coating and annealing a material including the electron transport paste.
[0079] Optionally, the thickness of the electron transport layer is 10 nm to 100 nm. Optionally, the thickness of the electron transport layer is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0080] Optionally, the electron transport layer is obtained by spin coating and annealing a material including the above-mentioned electron transport paste.
[0081] Optionally, the first electrode is a transparent electrode or a metal electrode. The second electrode is a transparent electrode or a metal electrode. Further, optionally, the first electrode and the second electrode are different. Optionally, the transparent electrode is a transparent glass electrode.
[0082] In some embodiments, the first electrode is typically transparent conductive glass. Optionally, the first electrode is selected from at least one of fluorine-doped tin oxide (FTO), indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), indium zinc oxide (IZO), and indium tungsten oxide (IWO). Optionally, the first electrode layer has a thickness of 100 nm to 1000 nm, optionally 300 nm to 800 nm.
[0083] In some embodiments, the second electrode is typically a metal electrode. Optionally, the second electrode is selected from at least one of Au, Ag, Cu, Al, Ni, Cr, Bi, Pt, Mg, Mo, W, and alloys thereof. Optionally, the thickness of the second electrode is 20 nm to 200 nm, optionally 60 nm to 100 nm, and further optionally 70 nm to 90 nm. It is understood that the perovskite layer is a light absorbing layer composed of a perovskite material. Optionally, the chemical formula of the material of the perovskite layer is ABX3 or A2CDX6, wherein:
[0084] A is an inorganic or organic or organic-inorganic mixed cation, comprising at least one of an organic amine cation, a Cs cation, a K cation, a Rb cation and a Li cation; the organic amine cation is selected from (NR1R2R3R4) + 、(R1R2N=CR3R4) + 、(R1R2N-C(R5)=NR3R4) + or (R1R2N-C(NR5R6)=R3R4) + , wherein R1, R2, R3, R4, R5 and R6 are each independently selected from H, substituted or unsubstituted C1-20 alkyl or substituted or unsubstituted aryl; A is optionally methylamino (CH3NH3 + )(MA + ), carbamimidyl (HC(NH2)2 + )(FA + ), cesium ions (Cs +) and rubidium (Rb + ), further optionally methylamino (CH3NH3 + ) or carboxamidino (HC(NH2)2 + ).
[0085] B is an inorganic or organic or organic-inorganic mixed cation, including at least one of lead, tin, zinc, titanium, antimony, bismuth, nickel, iron, cobalt, silver, copper, gallium, germanium, magnesium, calcium, indium, aluminum, manganese, chromium, molybdenum and europium, and optionally a divalent metal ion Pb 2+ and Sn 2+ At least one of .
[0086] C is an inorganic, organic, or organic-inorganic mixed cation, optionally a monovalent metal ion Ag. + wait.
[0087] D is an inorganic or organic or organic-inorganic mixed cation, optionally a trivalent metal ion bismuth cation Bi 3+ 、Antimony cation Sb 3+ 、Indium cation In 3+ wait.
[0088] X is an inorganic or organic or organic-inorganic mixed anion, optionally one or more of a halogen anion and a carboxylate anion, and further optionally a bromide ion (Br - ) or iodide ion (I - ).
[0089] In some embodiments, the perovskite layer has a band gap of 1.20 eV to 2.30 eV.
[0090] In some embodiments, the thickness of the perovskite layer is 200 nm to 800 nm, and optionally 400 nm to 600 nm.
[0091] In some embodiments, the perovskite solar cell further comprises a hole transport layer, which is located between the first electrode and the perovskite layer. Optionally, the hole transport layer can be at least one of the following materials and their derivatives and materials obtained by doping or passivation: poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), poly-3 hexylthiophene (P3HT), triphenylamine with triptycene as the core (H101), 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), N- (4-anilino) carbazole-spirobifluorene (CzPAF-SBF), poly (3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT:PSS), polythiophene, nickel oxide (NiO x ), molybdenum oxide (MoO3), cuprous iodide (CuI), cuprous oxide (CuO), etc.
[0092] In some embodiments, the perovskite solar cell further comprises a first passivation layer, the first passivation layer being located between the perovskite layer and the hole transport layer. Optionally, the material of the first passivation layer is PTAA.
[0093] In some embodiments, the perovskite solar cell further comprises a second passivation layer and / or a buffer layer, the second passivation layer and / or the buffer layer being located between the electron transport layer and the second electrode. Optionally, the second passivation layer and the buffer layer are made of bathocuproine (BCP).
[0094] It can be understood that perovskite solar cells include formal perovskite solar cells and inverse perovskite solar cells. For formal perovskite solar cells, the formal perovskite solar cell includes a transparent electrode and an electron transport layer, a perovskite layer, a hole transport layer and a metal electrode sequentially stacked on the transparent electrode. For inverse perovskite solar cells, the inverse perovskite solar cell includes a transparent electrode and a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode sequentially stacked on the transparent electrode. In the present application, the corresponding formal perovskite solar cell and inverse perovskite solar cell can be obtained by selecting the materials of the first electrode and the second electrode.
[0095] Please refer to Figure 1, which shows the structure of a perovskite solar cell in one embodiment of the present application. The first electrode is FTO, on which a hole transport layer, a passivation layer, a perovskite layer, an electron transport layer, a passivation layer or buffer layer, and a metal electrode are sequentially stacked. A glass substrate is placed on the surface of the FTO away from the perovskite layer.
[0096] The present application also provides a method for preparing a perovskite solar cell. The method comprises the following steps: preparing a perovskite layer on a first electrode; preparing an electron transport layer on the perovskite layer; and preparing a second electrode on the electron transport layer. The electron transport layer comprises a fullerene composite material, the fullerene composite material comprising a host material and a dopant material, the host material comprising a first fullerene derivative, the dopant material being selected from at least one of a fullerene and a second fullerene derivative, the molecular structure of the dopant material being partially embedded in the lattice of the first fullerene derivative.
[0097] Optionally, the perovskite layer is prepared by spin coating and annealing. Optionally, the electron transport layer is prepared by spin coating and annealing. Optionally, the second electrode is prepared by evaporation.
[0098] Optionally, the electron transport layer is prepared by spin coating the electron transport slurry and annealing.
[0099] The present application also provides an electrical device. The electrical device includes the aforementioned perovskite solar cell. Optionally, the electrical device is an electrical device used in, for example, the communications, transportation, industrial and agricultural, or lighting fields. Examples of electrical devices include satellites, communications equipment, traffic lights, lighthouses, wireless telephone booths, oil drilling monitoring equipment, power supply systems, camping lanterns, electric vehicles, and electronic device chargers.
[0100] Example
[0101] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0102] Example 1
[0103] The preparation steps of the fullerene composite material in this embodiment are as follows:
[0104] S101: Synthesis of methyl 4-benzoylbutyrate:
[0105] Take a 500mL clean and dry two-necked flask, add 19.25g (0.1mol) of benzoylbutyric acid, dissolve it in 300mL of chlorobenzene, add 100mL of methanol, stir until completely dissolved, add 30mL of hydrochloric acid dropwise, continue stirring, heat under reflux to react overnight, point the plate to determine that the reaction is complete, then stop stirring, neutralize with saturated sodium carbonate until there are no bubbles, separate the oil and water, and then extract the aqueous phase with ethyl acetate, combine the organic phases, remove water with anhydrous calcium chloride, and distill under reduced pressure to remove the solvent. Elute and separate the product on a silica gel column with ethyl acetate / n-hexane (volume ratio 3:1) as the eluent to obtain 18g of methyl 4-benzoylbutyrate as a light yellow oily liquid.
[0106] S102: Synthesis of methyl 5-phenyl-5-(p-toluenesulfonylhydrazide)valerate:
[0107] 10.5 g (0.05 mol) of methyl 4-benzoylbutyrate, 11.5 g (0.06 mol) of p-toluenesulfonylhydrazide and 200 ml of methanol were heated to reflux in a single-necked round-bottom flask, reacted for 12 h, cooled to room temperature, stored in the dark for 24 h, then transferred to -15 ° C in the dark overnight, filtered, and the product was recrystallized in methanol. The product was vacuum-treated at 40 ° C overnight to obtain 18.2 g of methyl 5-phenyl-5-(p-toluenesulfonylhydrazide) valerate as a white solid.
[0108] S103: Synthesis of F1-OMe:
[0109] Take a clean and dry 1L three-necked flask, dissolve 11.25g (0.03mol) of 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate in 250mL of pyridine, add 1.75g of sodium methoxide, stir, evacuate, and keep it under argon atmosphere. Take another clean and dry round-bottom flask, add 10.8g of C60, dissolve it in 300mL of o-dichlorobenzene, and add it dropwise to the above three-necked flask. Heat and reflux for 24h, evaporate the product to remove most of the solvent, and separate the product by column chromatography to obtain 6.83g of product F1-OMe.
[0110] S104: Fullerene composite materials:
[0111] 6.83g of F1-OMe and dopant material C50 were dissolved in o-dichlorobenzene and heated under reflux for 48 hours. The product was concentrated and then added to methanol for precipitation to obtain a fullerene composite material. In this example, the dopant material was C50 and the host material was PC61BM. The dopant material C50 accounted for 0.1% by mass of the fullerene composite material, i.e., the doping amount was 0.1%.
[0112] The perovskite solar cell in this embodiment is prepared in the following steps:
[0113] S201: Take 20 pieces of FTO conductive glass with a specification of 2.0cm*2.0cm, remove 0.35cm of FTO at both ends by laser etching, and expose the glass substrate; ultrasonically clean the etched FTO conductive glass with water, acetone, and isopropyl alcohol in sequence; blow the cleaned FTO conductive glass dry with a nitrogen gun, and place it in a UV ozone machine for UV ozone cleaning.
[0114] S202: 10 mg / mL nickel oxide nanoparticles (water as solvent) are spin-coated on the FTO substrate after UV ozone cleaning at a rate of 4000 rpm and annealed on a hot plate at 100° C. for 30 minutes to form a hole transport layer.
[0115] S203: PTAA was dissolved in chlorobenzene at a concentration of 1 mg / mL, and filtered through a 0.45 μm filter membrane after stirring. 50 μL was dropped onto the hole transport layer, and the mixture was spin-coated at a speed of 4000 rpm. The mixture was annealed on a hot plate at 100°C for 10 minutes to obtain a passivation layer.
[0116] S204: Weigh 223 mg of lead iodide PbI2, 80 mg of iodomethanesulfonate FAI, and 15 mg of chloromethylamine (MACl) and dissolve them in a mixed solution of 0.8 mL of DMF and 0.2 mL of DMSO. Stir for 3 hours and filter with a 0.22 μm organic filter membrane to obtain a perovskite precursor solution. Spin coat the perovskite precursor solution on the passivation layer at 3000 rpm, anneal at 120°C for 30 minutes, and cool to room temperature to form a perovskite layer, wherein the active substance in the perovskite layer is the FA system and the thickness is 500 nm.
[0117] S205: The fullerene composite material obtained in S104 is dissolved in chlorobenzene to form an electron transport slurry with a concentration of 20 mg / mL. The electron transport slurry is spin-coated on the perovskite layer at 1500 rpm and annealed at 100°C for 10 minutes to form an electron transport layer with a thickness of 50 nm. Next, a passivation material BCP solution is spin-coated at 5000 rpm, wherein the BCP solution is BCP dissolved in isopropyl alcohol with a concentration of 0.5 mg / mL to form a passivation layer with a thickness of 5 nm. The perovskite solar cell is then placed in an evaporation machine and a metal electrode Ag is evaporated to obtain a perovskite solar cell.
[0118] Example 2
[0119] Compared with Example 1, the difference of this embodiment is that the doping material is PC51BM. The PC51BM is prepared by S101 to S103 in Example 1, except that C60 in S103 is replaced by C50.
[0120] When preparing the fullerene composite material, the doping material C50 in S104 in Example 1 was replaced with PC51BM.
[0121] In this embodiment, the doping material is PC51BM, and the main material is PC61BM. In the obtained fullerene composite material, the mass percentage of the doping material PC51BM in the fullerene composite material is 0.05%, that is, the doping amount is 0.05%.
[0122] Example 3
[0123] Compared with Example 1, the difference of this embodiment is that C60 in S103 is replaced by C50 and C60, wherein the sum of the masses of C50 and C60 is equal to the mass of C60 in S103 in Example 1, and the mass percentage of C50 is 0.1% as a percentage of the total mass of C50 and C60.
[0124] In this embodiment, the doping material is PC51BM, and the main material is PC61BM. In the obtained fullerene composite material, the mass percentage of the doping material PC51BM in the fullerene composite material is 0.05%, that is, the doping amount is 0.05%.
[0125] Example 4
[0126] Compared with Example 1, the difference of this embodiment is that C60 in S103 is replaced by C50, C60 and C70, wherein the sum of the masses of C50, C60 and C70 is equal to the mass of C60 in S103 in Example 1, and the mass percentage of C50 is 0.1%, and the mass percentage of C70 is 0.03% as a percentage of the total mass of C50, C60 and C70.
[0127] In this example, the doping materials are PC51BM and PC71BM, and the main material is PC61BM. In the resulting fullerene composite material, the doping material PC51BM accounts for 0.05% by mass of the fullerene composite material, and the doping material PC71BM accounts for 0.015% by mass of the fullerene composite material. This means that the doping amount of PC51BM is 0.05%, and the doping amount of PC71BM is 0.03%.
[0128] Example 5
[0129] Compared with Example 1, this embodiment differs in that the amount of dopant material C50 added in S104 is adjusted. The dopant material is C50, the main material is PC61BM, and the mass percentage of the dopant material C50 in the obtained fullerene composite material is 0.0001%.
[0130] Example 6
[0131] Compared with Example 1, this embodiment differs in that the amount of dopant material C50 added in S104 is adjusted. The dopant material is C50, the main material is PC61BM, and the mass percentage of the dopant material C50 in the obtained fullerene composite material is 1%.
[0132] Example 7
[0133] Compared with Example 1, the difference of this embodiment is that C50 is replaced by C70.
[0134] Example 8
[0135] Compared with Example 1, this embodiment differs in that the amount of dopant material C50 added in S104 is adjusted. The dopant material is C50, the main material is PC61BM, and the mass percentage of the dopant material C50 in the obtained fullerene composite material is 0.00005%.
[0136] Example 9
[0137] Compared with Example 1, this embodiment differs in that the amount of dopant material C50 added in S104 is adjusted. The dopant material is C50, the main material is PC61BM, and the mass percentage of the dopant material C50 in the obtained fullerene composite material is 1.3%.
[0138] Example 10
[0139] Compared to Example 1, this Example differs in that Steps S101 to S103 are not performed. In S104, C60 and the dopant material C50 are dissolved in o-dichlorobenzene, heated under reflux for 48 hours, and the product is concentrated and then added to methanol for precipitation to obtain a fullerene composite material. The dopant material is C50, and the main material is C60. In the obtained fullerene composite material, the dopant material C50 accounts for 0.1% by weight of the fullerene composite material.
[0140] Comparative Example 1
[0141] Compared with Example 1, the difference of this comparative example is that C50 is not added to S104, that is, PC61BM is not doped.
[0142] Comparative Example 2
[0143] Compared with Example 1, this comparative example is different in that PC61BM and C50 are directly mixed to obtain a fullerene composite material, wherein the mass percentage of C50 in the fullerene composite material is 0.1%.
[0144] Comparative Example 3
[0145] Compared with Example 1, the fullerene composite material was not prepared, and the electron transport layer was prepared in the perovskite solar cell by evaporating C60.
[0146] Test example:
[0147] Under standard simulated sunlight (AM 1.5G, 100mW / cm 2 ) irradiation, the battery performance is tested and the IV curve is obtained. According to the IV curve and the data fed back by the test equipment, the short-circuit current Jsc (unit: mA / cm 2 ), open-circuit voltage Voc (V), maximum optical output current Jmpp (mA), and maximum optical output voltage Vmpp (V). The cell's fill factor (FF) (in %) is calculated using the formula FF = Jsc × Voc / (Jmpp × Vmpp). The cell's photoelectric conversion efficiency (PCE) (in %) is calculated using the formula PCE = Jsc × Voc × FF / Pw, where Pw represents the input power (in mW).
[0148] The doping amounts of the doping materials and the test results of the batteries in the examples and comparative examples are shown in Table 1.
[0149] Table 1
[0150] As can be seen from Table 1, the perovskite solar cell in the embodiment achieves a higher photoelectric conversion efficiency than the comparative example. For example, it can be seen from the embodiment, comparative example 1, and comparative example 3 that the perovskite solar cell in which the electron transport layer includes a doping material has a higher photoelectric conversion efficiency. It can be seen from Example 1 and comparative example 2 that compared with the method of directly mixing PC61BM and C50, the fullerene composite material obtained by the preparation method in Example 1 is applied to the electron transport layer, and the resulting perovskite solar cell has a higher photoelectric conversion efficiency. At the same time, when the mass percentage of the doping material in the fullerene composite material is 0.0001% to 1%, the perovskite solar cell can achieve a higher photoelectric conversion efficiency.
[0151] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A fullerene composite material, It is characterized in that It includes a main material and a doping material, wherein the main material includes at least one of a first fullerene and a first fullerene derivative, the doping material is selected from at least one of a second fullerene and a second fullerene derivative, and a molecular structure of the doping material has a partial structure embedded in the lattice of the first fullerene and / or the first fullerene derivative.
2. The fullerene composite material according to claim 1, It is characterized in that Calculated as a percentage of the total mass of the first fullerene and / or the first fullerene derivative and the doping material, the mass percentage of the doping material is 0.0001% to 1%.
3. The fullerene composite material according to any one of claims 1 to 2, It is characterized in that The first fullerene includes at least one of C50, C60 and C70, and the first fullerene derivative includes at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM and PC72BM.
4. The fullerene composite material according to any one of claims 1 to 3, It is characterized in that The second fullerene includes at least one of C50, C60 and C70, and the second fullerene derivative includes at least one of PC51BM, PC52BM, PC61BM, PC62BM, PC71BM and PC72BM.
5. A method for preparing a fullerene composite material, It is characterized in that The steps include: Mixing the first raw material and the second raw material in a first solvent, and heat-treating the obtained mixed system; The first raw material contains a first fullerene and / or a first fullerene derivative and / or a raw material for synthesizing the first fullerene derivative, and the second raw material contains at least one of a second fullerene and a second fullerene derivative used as a doping material.
6. The method for preparing the fullerene composite material according to claim 5, It is characterized in that The raw materials for synthesizing the first fullerene derivative include a third fullerene, 5-phenyl-5-(p-toluenesulfonylhydrazide) methyl pentanoate and a base; mixing the first raw material and the second raw material in a solvent includes: The 5-phenyl-5-(p-toluenesulfonylhydrazide)pentanoic acid methyl ester and the base are dispersed in a first sub-solvent, the second raw material and the third fullerene are dispersed in a second sub-solvent, and the two solution systems are mixed.
7. The method for preparing the fullerene composite material according to claim 6, It is characterized in that The molar ratio of the third fullerene, the doping material, the 5-phenyl-5-(p-toluenesulfonylhydrazide)pentanoic acid methyl ester and the base is 1:(10 -5 ~10 -2 ):(1~2):(1~10).
8. The method for preparing the fullerene composite material according to any one of claims 6 to 7, It is characterized in that The first sub-solvent comprises pyridine; and / or, The second sub-solvent includes at least one of toluene, xylene, chlorobenzene and dichlorobenzene; and / or, The base includes at least one of sodium methoxide, cesium carbonate, sodium hydroxide and potassium hydroxide.
9. The method for preparing the fullerene composite material according to any one of claims 5 to 8, It is characterized in that The first solvent includes at least one of toluene, xylene, chlorobenzene and dichlorobenzene.
10. The method for preparing the fullerene composite material according to any one of claims 5 to 8, It is characterized in that The heat treatment satisfies at least one of the following characteristics: (1) The temperature of the heat treatment is 100° C. to 300° C.; (2) The heat treatment time is 24h to 60h; (3) The heat treatment includes heating under reflux.
11. A perovskite solar cell, It is characterized in that It includes a first electrode, a perovskite layer, an electron transport layer and a second electrode which are stacked in sequence; The electron transport layer comprises the fullerene composite material according to any one of claims 1 to 4, or The electron transport layer comprises the fullerene composite material obtained by the preparation method according to any one of claims 5 to 10.
12. The perovskite solar cell according to claim 11, It is characterized in that The thickness of the electron transport layer is 10 nm to 100 nm.
13. A method for preparing a perovskite solar cell, It is characterized in that The steps include: forming a perovskite layer on the first electrode; preparing an electron transport layer on the perovskite layer; preparing a second electrode on the electron transport layer; The electron transport layer includes a fullerene composite material, which includes a main material and a doping material. The main material includes at least one of a first fullerene and a first fullerene derivative, and the doping material is selected from at least one of a second fullerene and a second fullerene derivative. The molecular structure of the doping material has a partial structure embedded in the lattice of the first fullerene and / or the first fullerene derivative.
14. An electrical device, It is characterized in that A perovskite solar cell comprising the perovskite solar cell according to any one of claims 11 to 12.
Citation Information
Patent Citations
Bacterial cellulose / fullerene composite material and preparation method thereof
CN106519307A
Application of alcohol soluble fullerene derivative in perovskite solar cell
CN107394047A
Application of fullerene methylene derivative I in perovskite solar cells, perovskite solar cell and preparation method thereof
CN109698280A
Application of phenol-substituted fullerene derivative in perovskite solar cell, perovskite solar cell and preparation method of perovskite solar cell
CN109742245A
Structure for improving thermal stability of bulk heterojunction solar cells and related photovoltaic apparatus and method for making the same
US20140116510A1
Cited By
PCBM, preparation method and application thereof, and device for preparing PCBM
CN120463596A